ENGLISH-FOR-TOURISM TRAINING TO IMPROVE THE ENGLISH CAPABILITY OF TOURISM WORKERS AND BUSINESS OWNERS IN THE DEPARTMENT OF TOURISM, CULTURE, YOUTH, AND SPORTS OF BLITARREGENCY: PELATIHAN ENGLISH FOR TOURISM UNTUK MENINGKATKAN KEMAMPUANBAHASA INGGRIS PARA PENGELOLA DESTINASI DAN USAHA WISATA DI DINAS PARIWISATA, KEBUDAYAAN, PEMUDA, DAN OLAHRAGA KABUPATEN BLITAR - Sidarta Prassetyo; Triubaida Maya Ardianti; Lutfi Ashar Mauludin; Annysa Endriastuti; Celya Intan Kharisma Putri (Faculty of Vocational Studies, Universitas Airlangga, 2023)
English plays a vital role in the tourism field since it supports tourism workers and business owners to provide excellent services. Numerous tourism destinations in Indonesia including the ones in Blitar Regency have become the center of attention for foreign tourists. Located in Blitar, East Java, Kampung Coklat and Karanganyar Coffee Plantation have also been continuously preparing their workers and business owners to provide efficient services for both domestic and foreign visitors. In accordance with providing excellent services to foreign tourists, tourism workers and business owners are expected to have good English mastery. Objectives: This community service aims to provide a support for the tourism workers and business owners under the supervision of the Department of Tourism, Culture, Youth, and Sports and the Department of Tourism Promotion of Blitar Regency in terms of improving their English mastery, especially their communication skills in English. Methods: The activity was carried out in three stages, namely two material sessions, speaking activities, and feedback. Results: This activity gave the participants an opportunity to practice serving a customer in English. Even though it was quite challenging for some of the participants, they felt encouraged to actively participate in the speaking activities and get familiar with expressions used in tourism and hospitality services. Conclusion: The supervision and training sessions in speaking English was very enlightening for the participants to improve their English mastery in tourism services. It needs a continuation to provide greater impact to the targeted participants.